A Fuzzy Based Sensor Web for Adaptive Prediction Framework to Enhance the Availability of Web Service. (14th February 2016) - Ramalingam, Sundharam; Mohandas, Lakshmi
Present day businesses revolve around internet applications (e.g., e-commerce, e-business, and internet banking) which are primarily supported by web services . The increasing consumer reliance on these internet-based applications causes dynamic variation in the number of requests received by web services and a slowdown in response time during peak load periods. To overcome this difficulty, in this paper, we propose a fuzzy logic (FL) based prediction and replication framework to replicate the web services over distributed servers and achieve timely responses. This framework senses the proximity of future interval response time against agreed service level agreement (SLA) time using sensor web called proximity sensor service. Also, it determines the replication requirement using FL and implements the FL decision using resource control algorithm to replicate the web service on another server before the SLA time is violated or to reclaim the excess resource. We conduct appropriate test scenarios in a dedicated test environment and compare the results with existing models. The results show that our framework replicates the web service at more appropriate times than the existing models and achieves 82% prediction accuracy. Thus, our framework significantly improves the availability of web services with minimal intervention from system administrators.